DAMPAK PROGRAM TERAPI RUMATAN METADON (PTRM) TERHADAP PASIEN PTRM DI SATELIT PELAYANAN PTRM PROVINSI DIY - , Julaeha; , dr. Sulanto Saleh Danu, SP.FK ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Methadone Maintenance Treatment Program (MMTP) is one of the harm reduction program. MMTP is expected to reduce drug use, risk behavior, crime, and increase productivity, living conditions, and family support for injecting drug users (IDUs). MMTP in Yogyakarta has been implemented since 2006. Currently have been provided four MMTP satellite services are: Grhasia hospital, Gedongtengen primary health care (PHC), Umbulharjo I PHC and Banguntapan II PHC. As of November 2012 there were 39 actively registered patients (35 males, 4 females). Thirty-two patients voluntarily participated in this study. Objective: To determine the impact of MMTP on patients, including a reduction in drug use, risk behavior, crime, and increase productivity, housing conditions, and family support in the MMTP satellite services Yogyakarta. Method: Descriptive research with case study design and cross-sectional approach. This research conducted in October - December 2012. Subjects were 32 MMTP active patients. The independent variable is implementation of MMTP services and dependent variable is the impact of MMTP. The research instruments use questionnaires and interview guides. Indicators of achievement PTRM impact of each parameter being measured in drug usage, high risk behaviours, criminal behaviours, and improvement in housing conditions and familiy support. Pearson correlation analysis to determine the relationship between MMTP services with the impact of MMTP on patients. Result: fifty-three (53%) were not using drug, 88% reduction in drug use, 78% were not using needles, 97% were not sharing needles, 97% were not involving in criminal activity, 100% reduction in criminal behaviours, 81% improvement in employment status, 91% improvement in housing conditions, 91% were getting family support, 84% increase in family support. The analysis result of of Pearson correlation was found significance level of 0,001 (< 0,05). With relationship value of 0,588. There was a significant positive relationship between MMTP services with the impact of MMTP on patients. Conclusion: MMTP is beneficial in harm reduction due to injecting drug use.